(untitled) (Journal of Surgical Sciences, 2020)
Background: A breast lump is the most common symptom associated with both benign and malignant breast diseases. Therefore, a distinction of benign from malignant lump is of importance for proper management. Though a definitive diagnosis is possible with imaging for all the lesions, histopathological study is proven essential for confirming the diagnosis. Objective: The objective of this study was to evaluate the role of USG and histopathological findings of different breast lump in diagnosis and their comparison. Methods: A prospective study was conducted over a period of one year from January 2017 to December 2017. A total of 116 patients were included in this study. All breast lumps underwent surgery and the ultrasound findings of these lumps were compared with the histopathological findings. Data were collected from these patients by a preformed questionnaire and finally the data were analyzed. Results: Out of 116 patients only 21 cases were reported as malignant in ultrasound report but histopathology revealed 31 malignant patients. On histopathological examination 10 benign cases turned out to be malignant. Conclusion: The present study was undertaken to evaluate in diagnosing breast mass lesions individually by ultrasound and compared with histopathology for definitive management of a patient. Journal of Surgical Sciences (2019) Vol. 23 (1) : 10-12